Dual blockade of IL‐4 and IL‐13 with dupilumab, an IL‐4Rα antibody, is required to broadly inhibit type 2 inflammation - Le Floc’h, Audrey; Allinne, Jeanne; Nagashima, Kirsten; Scott, George; Birchard, Dylan; Asrat, Seblewongel; Bai, Yu; Lim, Wei Keat; Martin, Joel; Huang, Tammy; Potocky, Terra B.; Kim, Jee H.; et al. (Allergy (Copenhagen), 2020)
Background Dupilumab, a fully human monoclonal antibody that binds IL‐4Rα and inhibits signaling of both IL‐4 and IL‐13, has shown efficacy across multiple diseases with underlying type 2 signatures and is approved for treatment of asthma, atopic dermatitis, and chronic sinusitis with nasal polyposis. We sought to provide a comprehensive analysis of the redundant and distinct roles of IL‐4 and IL‐13 in type 2 inflammation and report dupilumab mechanisms of action. Methods Using primary cell assays and a mouse model of house dust mite–induced asthma, we compared IL‐4 vs IL‐13 vs IL‐4Rα blockers. Results Intranasal administration of either IL‐4 or IL‐13 confers an asthma‐like phenotype in mice by inducing immune cell lung infiltration, including eosinophils, increasing cytokine/chemokine expression and mucus production, thus demonstrating redundant functions of these cytokines. We further teased out their respective contributions using human in vitro culture systems. Then, in a mouse asthma model by comparing in head‐to‐head studies, either IL‐4 or IL‐13 inhibition to dual IL‐4/IL‐13 inhibition, we demonstrate that blockade of both IL‐4 and IL‐13 is required to broadly block type 2 inflammation, which translates to protection from allergen‐induced lung function impairment. Notably, only dual IL‐4/IL‐13 blockade prevented eosinophil infiltration into lung tissue without affecting circulating eosinophils, demonstrating that tissue, but not circulating eosinophils, contributes to disease pathology. Conclusions Overall, these data support IL‐4 and IL‐13 as key drivers of type 2 inflammation and help provide insight into the therapeutic mechanism of dupilumab, a dual IL‐4/IL‐13 blocker, in multiple type 2 diseases. The IL‐4Rα antibody, dupilumab, binds IL‐4Rα with high affinity, directly blocks IL‐4 and IL‐13/IL‐13Rα1 complex binding to IL‐4Rα, and thereby prevents IL‐4Rα‐mediated signaling induced by both IL‐4 and IL‐13. IL‐4 and IL‐13 play distinct and overlapping roles and blockade of both cytokines is required to broadly block type 2 inflammation, which translates to protection from allergen‐induced lung function impairment. Only dual IL‐4/IL‐13 blockade with dupilumab prevents eosinophil infiltration into lung tissue without affecting circulating eosinophils, demonstrating that tissue, but not circulating eosinophils contribute to disease pathology.